Focus variation measurement of electron beam melted surfaces - Newton, Lewis; Senin, Nicola; Leach, Richard (2017)
Electron beam melting (EBM) is a promising additive manufacturing process which is seeing increasing use in high value manufacturing sectors such as aerospace [1]. With its layer-by-layer approach, EBM can allow the creation of parts of complex shapes, thus reducing the need for assembly [2]. Surface topography measurement of EBM parts is gaining an increasingly important role, both for assessing the surface finishes that can be obtained with the process before and after post-processing, and as a useful tool to investigate how the manufacturing process behaves through the observation of surface features produced (observation of the manufacturing process signature or fingerprint) [3]. EBM surfaces are very complex and irregular, with a large number of high slopes and undercuts [4]. It is, therefore, very difficult to measure the surface topography of an EBM part. Optical technologies for areal topography measurement are now popular, thanks to their capability for fast acquisition of dense data sets [5]. Focus variation (FV) is one of the most promising measurement technologies for EBM parts, as it combines reasonably fast measurement times with good capability to capture complex topographies [6]. However, many possible FV set-ups could be adopted for measuring an EBM surface. Objective lens magnification, illumination conditions and detector parameters are some of the most relevant control variables that can be varied, in the attempt to achieve optimal measurement results.